2021
DOI: 10.1096/fj.202100145r
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps contribute to immune dysregulation in bullous pemphigoid via inducing B‐cell differentiation and antibody production

Abstract: Bullous pemphigoid (BP), an autoimmune skin disease, is characterized by autoantibodies against hemidesmosomal proteins in the skin and mucous membranes. Neutrophils infiltrate BP skin lesions, however, their role in immune dysregulation remains unclear. We investigated whether BP involves aberrant neutrophil extracellular traps (NETs) formation in skin lesions and circulation; and examined the triggers and deleterious immuno‐inflammatory consequences. In the present study, we found that circulating NET‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
(118 reference statements)
0
21
0
1
Order By: Relevance
“…Using immunodetection of patient skin biopsies, NET formation has been shown to be associated with BP ( 101 ). Additionally, levels of NET biomarkers are correlated to BP disease activity ( 102 ). Thus, it is likely that these complexes play a role in the tissue damage involved in this disease.…”
Section: Eosinophil and Ige Mediated Blisteringmentioning
confidence: 99%
“…Using immunodetection of patient skin biopsies, NET formation has been shown to be associated with BP ( 101 ). Additionally, levels of NET biomarkers are correlated to BP disease activity ( 102 ). Thus, it is likely that these complexes play a role in the tissue damage involved in this disease.…”
Section: Eosinophil and Ige Mediated Blisteringmentioning
confidence: 99%
“…Neutrophils and eosinophils also regulate different aspects of BP inflammation. As an example, NET release from neutrophils acts systemically by inducing B-cell differentiation into plasma cells via activation of the MAPK/p38 cascade (109). Eosinophils mediate specific IgE pathogenicity, release cytokines which enhance Th2 cell recruitment and stimulate peripheral nerve terminals, e.g., by releasing IL-31 (88,(110)(111)(112).…”
Section: Cytokine Regulation Of Non T/b Immune Cells In Bullous Pemph...mentioning
confidence: 99%
“…The antitumor response mainly depends on APCs to prime naïve T cells ( 171 ). Various studies have reported that the cDC1 subset is associated with the induction of tumor-controlling immunity and improved overall survival in many tumor types ( 172 , 173 ). The activation of neutrophils releases the granule content neutrophils elastase (NE) that induces the polarization of the DC-mediated development of T cells into Th 17 cells, while the blocking of neutrophil activation or NE prevents the production of Th 17 cells ( 174 ).…”
Section: Neutrophils As Immune Suppressormentioning
confidence: 99%